Exploring Women Empowerment Levels in Welenchiti Town, East-Central Ethiopia (Journal of Informatics Education and Research, 2024)
This study explores women's empowerment levels in Welenchiti Town, East-Central Ethiopia, focusing on personal, psychological, and socio-cultural dimensions. Using a descriptive research design and a quantitative approach, data were collected from 363 women through questionnaires and analyzed using frequency, percentage, mean, and standard deviation. The findings reveal that women in Welenchiti Town exhibit high levels of personal empowerment, demonstrating autonomy in decisions related to healthcare access and financial contributions, although constraints remain in terms of social participation. Psychologically, the women exhibit self-satisfaction and openness to new experiences, but gaps persist in their confidence and skills in public speaking, leadership, and expressing their opinions. Socio-culturally, the women actively engage in social services and combat harmful practices, yet challenges exist in resolving household conflicts and addressing societal oppression. To achieve holistic empowerment, the study recommends initiating partnerships between stakeholders to address cultural norms, enhance women's confidence and leadership skills, and equip them with tools to challenge the societal constraints they face.